AIDS-related Behaviour Change, Knowledge and Opinions Among First Year University Students - Loos, Cynthia; Bowd, Alan (Canadian Journal of Counselling and Psychotherapy, 2011)
This study examines knowledge about HIV transmission, opinions about AIDS-related social issues and concern about contracting AIDS among a group of first-year university students. Relationships with self-reported changes in sexual behaviour are described. Knowledge of transmission modes was high and most participants reported considering themselves well-informed. Halfclaimed that they practised "safer sex" but less than one-third discussed AIDS with partners. Among participants reporting higher frequency of sexual intercourse and multiple partners, there was only a marginal increase in more appropriate sexual practices. Participants reporting no concern about contracting AIDS were less likely to change their behaviour. Implications for AIDS education and broad counselling strategies in universities and colleges are briefly described.